Bridging Gaps In Energy Planning for First Nation Communities. Issue 3 (1st January 2018) - Rakshit, Roopa; Shahi, Chander; Smith, M.A. (Peggy); Cornwell, Adam
ABSTRACT: There is a link between energy security, economic prosperity, sustainability and sovereignty for indigenous communities in Canada. Geographically remote locations, absence of all-season roads, off-grid status, diesel dependency and lack of alternative energy access causes energy insecurities along with economic, social, and local environmental problems for the Keewaytinook Okimakanak (KO) First Nation communities in northwestern Ontario. Being free of diesel dependency and scoping sustainable energy solutions are immediate priorities. Both are key motivational factors for effective community energy planning (CEP). However, most CEP is based on top-down decision making approaches which lack effective community engagement to design culturally appropriate, community-centeric energy plans. Such approaches fail to acknowledge local socio-cultural drivers as indicators of energy planning. This article details the disconnects between theory and practice in energy planning for First Nation communities. The overarching purpose of this article is to bridge knowledge gaps regarding socio-cultural requirements, discuss the social costs in energy planning, and advance academic literature about indigenous perspectives on energy planning. A literature review, key informant interviews and in-field observations in KO First Nation communities form the basis of our study. This article examines community insights on local energy planning to elicit drivers and determinants for a conceptual, bottom-up energy planning framework. It offers recommendations to integrate socio-cultural factors as part of a sustainable and functional energy planning approach for the KO communities. It provides justification that this process ensures multiple benefits such as buy-in by the communities, acceptance, and readiness for CEP implementation which fosters community ownership, self-determination, pride and empowerment. The research findings are timely. There is growing interest in ensuring local energy security amidst longstanding colonial treatment and marginalization of indigenous communities in the broader context of Canada's greenhouse gas commitments.